Study of 3D binder-free silicide/silicon anodes for lithium-ion batteries - Cherf, Shiraz; Golodnitsky, Diana (Frontiers in Batteries and Electrochemistry, 2023)
Silicon anode materials have attracted much attention as an alternative to the graphite anode in Li-ion batteries since the theoretical capacity of silicon is an order of magnitude higher than that of graphite. However, the drastic volume changes of silicon during lithiation/delithiation cause breakup of the electrode, electrical isolation of the active material and capacity fade. Binders and conducting agents, while improving adhesion and electrical conductivity, reduce the volumetric capacity of the Si anodes. In this article, we present the study of improved, easy-to-fabricate binder-free 3D silicon anodes. The anodes are prepared by combining for the first time three approaches: use of Si nanoparticles, use of porous, high-surface-area metal foam current collector and formation of metal silicide layer in between. The fabrication of 3D anodes includes electrophoretic deposition of silicon nanoparticles (SiNP) on copper, nickel, and titanium foams followed by annealing at different temperatures and time. Analysis of morphology and electrochemical performance of composite 3D silicon/silicide anodes reveals that increased annealing time of SiNPs-deposited on Ni foam results in a thicker Ni3Si2 layer, which leads to the enhanced capacity retention and power capability. At C/10 and C/2 rates the reversible capacity of NMC/3DSi-Ni3Si2 cells was 880 and 530 mAh/gSi+Silicide, respectively.